(untitled) (Revista de Medicina Clinica, 2018)
Introduction: Upper gastrointestinal bleeding has an incidence of 100/100,000 per year and is one of the main causes of hospitalization in surgical services. UGB has a mortality of 6-10%, most cases due to peptic ulcer (80%). In Mexico, information is scarce. The objective was to identify morbidity and mortality in patients with UGB who required surgery and were treated at the â€œHospital de Alta Especialidad, Centro MÃ©dico Nacional d Occidenteâ€. Materials and Methods: A retrospective study was conducted. The information was analyzed in the statistical program SPSS v15 . Measures of central tendency and dispersion were used; for categorical variables we used percentages and for numerical variables means with SD or median with maximum and minimum ranges. Results: 63 patients were included. There were 42 (67%) men and the average age was 60.9 +/- 12.03 years. The average time from hospital arrival to the completion of the surgery was 71.6 +/- 4.7 hours, patients need 4.7 +/- 1.3 globular in average. The main cause of UGB was peptic ulcer in 50% of cases, and the main surgical procedure used was suture at the site of bleeding in 55% of cases. The most frequent hospital complication was hemodynamic instability in 89%. We conclude that UGB that requires surgery is a medical emergency that endangers life since 89% of patients have hemodynamic instability, in addition, the main cause is peptic ulcer that has solution in most cases by suture at the site of bleeding.